Parenting Patterns Of Providing Food, Picky Eaters And Food Diversity Against Stunting Incidents In The Working Area Of Kamaipura Health Center Sigi Regency - Sukmawati Paju; Ni Ketut Kariani; Nurdiana, Nurdiana (Jurnal EduHealth, 2024)
Background: The World Health Organization (WHO) and UNICEF estimate the prevalence of stunting in the world at 23.3%, the prevalence of stunting in Indonesia at 21.5% and 26.4% in Central Sulawesi. Sigi Regency has the highest prevalence of stunting in 2022 at 27.2%. Kamaipura Community Health Center ranks highest at 43.6% in 2023 in Sigi Regency. The aim of this research is to analyze the relationship between parenting patterns of feeding, picky eaters and food diversity on the incidence of stunting in the Kamaipura Health Center working area, Sigi Regency. Method: This type of research is quantitative with an observational analytical approach using a cross sectional design . The population in this study were all toddlers aged 24-59 months totaling 219 toddlers with a sample of 58 stunted toddlers and The sampling technique uses simple random sampling. Research result: Based on the results of bivariate analysis using the Spearman test, all variables were related to the incidence of stunting with a value of (p<0.05) and based on multivariate analysis it was found that the food diversity variable contributed most to the incidence of stunting with the highest regression coefficient value (B=0.215). Conclusion: Most of the respondents had poor parenting patterns, were picky eaters and lacked food diversity. There is a relationship between parenting patterns, picky eaters and food diversity on the incidence of stunting and the variable that contributes most to the incidence of stunting is food diversity. Suggestion: For health workers at the Kamaipura Community Health Center, they will be more active in providing education, for the community they will pay more attention to children's nutritional intake and take part in education about nutrition, for future researchers they will add the characteristics of respondents and other variables to better support the research and prepare themselves better before going to the research site.